Respect PKU staff, our frontliners - UMP, PNC (2020)
Facing of the outbreak of the Covid-19 that has been declared a pandemic by the World Health Organization (WHO), the Center for Health (PKU), Universiti Malaysia Pahang (UMP) is always on alert to fight the spread of the outbreak in both university campuses.